Health financing, environmental quality and health outcomes: evidence from developing countries - Mohamed Nor, Norashidah; Lacheheb, Miloud; Law, Siong Hook; Raja Abdullah, Nik Mustapha (International Economic Society, 2016)
This paper attempts to investigate the impact of health financing and environmental quality on health outcome in low and lower-middle income countries using Generalized Method of Moments (GMM). Data were obtained from World Development Indicators and World Governance Indicators. Results based on system GMM reveal that health financing plays a positive role in stimulating life expectancy, whereas the reverse is observed if health is financed privately or from individuals’ out-of-pocket expenditure. At the same time, improved environmental quality is found to be an influential factor that can contribute to a better health condition. These findings enhance our understanding of good health as a product of the combination of different factors.